Legal Aspects of Cooperation Agreement in Health Insurance Between Hospitals and BPJS - Ernawati, Ni Luh Ade Kusuma; Manuaba , Ida Bagus Gede Fajar (Syntax Corporation Indonesia, 2024)
One of the social security efforts is health insurance. Health insurance is a guarantee of health care that is used as a transfer of risk of loss. Health insurance is realized by the government in the form of National Health Insurance (JKN) through the Social Security Organizing Agency (BPJS). Efforts to protect BPJS participants are the existence of a cooperation agreement between BPJS and health service providers including hospitals, health centers and other health service facilities. The type of research used is normative law. The data sources used are obtained through secondary data sources, namely indirect data sources. This research is explanatory in nature, namely by explaining how the cooperation between the BPJS Health and the Hospital and how also with the implementation of health insurance for national health insurance participants and efforts from th The results showed that the cooperation agreement between the hospital and BPJS Health in the National Health Insurance (JKN) program is important legal aspects that guarantee the rights and obligations of both parties and ensure the realization of quality health for BPJS Health participants. e BPJS Health in overcoming the financing of the National Health Insurance program.